Pengaruh Cara Pengemasan Terhadap Perubahan Mutu Buah Sawo (Manilkara Zapota (L.) Van Royen) Setelah Pengiriman - MUSLIM, Abedi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Harvested sapodilla (Manilkara zapota (L.) van Royen) fruits are usually distributed in sacks. This often causes a lot of fruit damage. This research tried to find out an alternative method of packaging sapodilla fruit better than using sacks. Various kinds of packaging methods i.e. sapodilla fruits in sack (control), cartons box, cartons box with partition between every layer of fruits, carton box with partition between every two layers of fruits, carton box with shredded newspapers as filler, cartons box with partition between every layer of fruits and shredded newspapers, and cartons box with partition between every two layers of fruits and shredded newspapers were arranged in completely randomized block design (rcbd) with three blocks as replications. The packages of fruits were transported for 4 hours than kept in room temperature of the Laboratory of Horticulture, Faculty of Agriculture Gadjah Mada University. The results showed that in general packaging sapodilla fruits in cartons box reduced fruit damage up to 5%, inhibited fruit quality decreasing, and prolonged shelf life of the fruits three days longer than control. The best packaging methods were carton box with partition between every layer of fruits and shredded newspapers, and carton box with partition between every two layers of fruits and shredded newspapers.